Counting the Soviet Nation: Population Politics Under Brezhnev - Lovett, Jessica E A (2023)
This thesis addresses a period in Soviet history when, for the first time, basic indicators of health and mortality worsened in a sustained way that could not be explained by a temporary disaster. Not only did this worsening occur in combination with very low birth rates among ethnic Russians, but it stood in contrast to the progress on mortality and longevity being made in the capitalist West. As such, the Brezhnev era (1964-1982) provided uncharted demographic territory for leaders of the Soviet Union. The aim of this work is to examine the political implications of this change and subsequent response. An enormous literature shows how economic dynamics affected the Soviet Union, but these works often see demographic dynamics as a side-note rather than a political force in their own right. This study seeks to address this, arguing for the significance of population change in shaping late-Soviet politics and culture.